PENGARUH PENDEKATAN COURSE REVIEW HORAY (CRH) TERHADAP PEMAHAMAN MATEMATIS DAN MOTIVASI BELAJAR MATEMATIKA SISWA SEKOLAH DASAR PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT - Suryani, Asih; Maulana, Maulana; Julia, Julia (Jurnal Pena Ilmiah, 2016)
One of purpose from this research is to know that course review horay (CRH) approach be better than conventional approach in an attempt increase of mathematical understanding and student’s motivation to learn math significanly. With the result that do use randomized control prettest posstest group desain of experiment research. The population are all elementary school in Sumedang Utara which one superior group, while the samples are SDN Rancapurut as experiment group and SDN Panyingkiran III as control group. The result of this research with P-Value is 5% (α = 0,05) known that CRH approach increases student’ mathematical understanding and motivation to learn math significanly. The other result is that CRH approach be better than conventional approach in an attempt increases of mathematical understanding and student’s motivation to learn math. That is seem of bigh positif responses from the student. Keyword: Course Review Horay (CRH) Approach, Mathematical Understanding, Motivation.